THE EFFECT OF ESG, ICD, AND PROFITABILITY ON FIRM VALUE WITH CORPORATE GOVERNANCE INDEX MODERATION - Aulia, Amalatul; Darmayanti, Novi; Zulkarnaen, Have; Irawan, Mohamad Rizal Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Transformation paradigm business from orientation profit going to sustainability put Environmental Social Governance (ESG), Intellectual Capital Disclosure (ICD), and profitability as indicator important in evaluate firm value. This study aims For analyze the influence of ESG, ICD, and profitability to firm value, as well as role Corporate Governance Index (CGI) as variables moderation in companies sector energy listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This study uses approach quantitative with method Partial Least Squares–Structural Equation Modeling (PLS-SEM). Research result show that ESG and profitability influential positive and significant to firm value, while ICD does not influential to firm value. CGI is also proven can strengthen connection between profitability to firm value whereas for ESG and ICD variables that are influenced by CGI not influential to firm vs. firm vs. firm. These findings underscore the importance of non-financial disclosure and corporate governance in shaping investor perceptions and improving market performance. The practical implications of this research are that companies need to strategically integrate ESG and ICD into their sustainability reports, while investors and regulators can utilize these indicators for more informed, sustainability-based decision-making.